Quality Management Contribution to Organisational Learning Dynamics: Case of a Moroccan SME Operating in the Agro-Food Sector (Economic and Political Thought, 2023)
The purpose of this article is to provide a framework for reflection, by descri- bing the role of quality management on organisational learning in Moroccan certified SMEs. After presenting a theoretical revue related to our main question, we will show the results of an exploratory study based on three different qualitative study methods (documentary study, semi-directive inte- rviews and non-participating observation) conducted on an agro-food SME. This analysis was carried out in two stages: first, by studying the specificity of the deployment of quality management in this SME, and then by examining the place of quality management in the dynamics of organisational learning and knowledge development.
Keywords: quality management, organisational learning, knowledge manage- ment, SME, Morocco, food industry